(untitled) (Global Journals of Research in Engineering, 2012)
Increased environmental concerns and depletion of fossil fuel resources necessitates the search for a viable alternative fuel for diesel engine. Bio-fuels are renewable, can supplement fossil fuel, reduce green house gas emissions and mitigate their adverse effects on the climate changes resulting from global warming. However, further reduction in engine emission becomes one of major tasks in engine development. One promising approach to solve this problem is to add the oxygenated fuels in biodiesel. Biodiesel commands crucial advantages such as technical feasibility of blending in any ratio with petroleum diesel fuel. Superiority from the environment and emission front, its capacity to provide energy security to remote and rural areas and employment generation. In this paper, the investigation is made with addition of biodiesel in different proportion and effect on engine performance and emissions were computed. The emission is found to be reduced considerably while the engine performance is also improved marginally.